Scleroderma overlap syndrome with interstitial lung disease and pulmonary artery hypertension. Issue 1 (February 2016) - Jangala, Mohan S.; Lomati, Venkata P.K.R.; Purma, Arvinda R.
الملخص: تعتبر متلازمة تداخل تصلب الجلد حالة نادرة تظهر على شكل اضطرابين أو أكثر من اضطرابات النسيج الضام لنفس المريض. يرتبط بعض أمراض النسيج الضام٬ بأجسام مضادة محددة الملامح٬ بينما الأخرى لا يظهر معها أي ارتباطات مصلية. نعرض لحالة متلازمة تداخل تصلب الجلد تعاني من حمى٬ وضيق التنفس٬ وتليف رئوي٬ وارتفاع ضغط الدم الرئوي٬ ومرض الرئة الخلالي، وفقر الدم والعلامات السريرية للتصلب الجهازي والتهاب المفاصل الروماتيزمي. في نفس الوقت٬ أظهرت النتائج المخبرية إيجابية قوية للأجسام المضادة للنواة والأجسام المضادة توبوايزوميريز-1٬ وإيجابية مصلية للحمى الروماتيزمية والأجسام المضادة. Abstract: Scleroderma overlap syndrome is a rare condition that presents as two or more connective tissue disorders in the same patient. Some of these connective tissue diseases are associated with a specific autoantibody profile, while others do not show any serological association. We report a case of a patient with scleroderma overlap syndrome who presented with fever, breathlessness, pulmonary fibrosis, pulmonary hypertension, interstitial lung disease, anaemia and clinical manifestations of systemic sclerosis and rheumatoid arthritis. The patient's laboratory results were strongly positive for antinuclear antibody (ANA) and anti-topoisomerase-1 antibody and seropositive for rheumatic fever and CCP antibodies.